Faktor Determinan Kinerja Keuangan pada Return Saham (Studi Kasus pada Perusahaan Perbankan di Indonesia) - Pradnyawati, Sagung Oka (Penerbit Goodwood, 2024)
Purpose: The purpose of this research is to test and analyze the determinant factors that can affect stock returns. Research methodology: Multiple linear regression analysis was used as a data analysis technique and probability method with purposive sampling was used to determine the research sample. Results: The conclusion of this research is that the operational ratio has a negative effect on stock returns, while the debt to equity ratio and net profit margin do not show a significant effect, while the investment opportunity set and economic value added have a positive effect on banking companies in Indonesia. Limitations: The research is only limited to the financial performance ratios used and the results given are focused on banking companies in Indonesia only. Contribution: This research can be used as a literature reference for further research, especially research on stock returns.